Wireless Body Area Networks for Healthcare Applications: An Overview - Muhammad Anwar; Abdul Hanan Abdullah; Kashif Naseer Qureshi; Abdul Hakeem Majid (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Healthcare systems have been facing various new challenges due to increasing and rising aging population in healthcare. Advance information and communication technologies have introduced Wireless Body Area Networks (WBANs) for healthcare systems. WBANs provide different monitoring services in healthcare sector for monitoring their patients with more convenience. WBANs are economical solutions and non-invasive technology for healthcare applications. This review paper provides a comprehensive review on WBANs applications, services and recent challenges.